Tobacco industry's elaborate attempts to control a global track and trace system and fundamentally undermine the Illicit Trade Protocol. Issue 2 (13th June 2018) - Gilmore, Anna B; Gallagher, Allen W A; Rowell, Andy
Abstract : Background: The Illicit Trade Protocol (ITP) requires a global track and trace (T&T) system to reduce tobacco smuggling. Given the tobacco industry's (TI) historical involvement in tobacco smuggling, it stipulates that T&T 'shall not be performed by or delegated to the tobacco industry'. This paper explores the rationale for & nature of the TI's effors to influence the ITP & its T&T system. Methods: Analysis of leaked TI documents and publicly available data;, investigation of front groups, trademark and patent ownership. Findings: Growing & diverse sources of evidence indicate that the TI remains involved in tobacco smuggling and that TI cigarettes account for around two-thirds of the illicit cigarette market. The TI therefore has a vested interest in controlling the global T&T system aimed to curtail this behaviour. To this end, Philip Morris International (PMI) adapted its pack marker system, Codentify, to meet T&T requirements, licensed it for free to its three major competitors who then collectively promoted it to governments using front groups and third parties including companies claiming to be independent despite clear TI links. PMI also sought to suggest Codentify was independent by selling some parts of its intellectual property on Codentify while retaining others, leaving a complex web of shared interests. In Africa, British American Tobacco used payments to obtain data suggesting its smaller competitor companies were evading taxes and secure influence with tax authorities. Regulatory capture has been enhanced by a public relations effort involving TI funding for conferences, training, research, and international police and anti-corruption organisations. Collectively this has created public messaging and a powerful network of organisations supportive of the TI's misleading postion on illicit. Conclusions: Governments should assume the TI seeks to control T&T systems in order to avoid scrutiny and minimise excise tax payments and that any T&T system based on Codentify, on intellectual property currently or previously owned by the TI, or being promoted or implemented by companies with TI links, is incompatible with the ITP and would not serve to reduce illicit trade.